Dentine matrix proteins: isolation and effects on human pulp cells. (14th March 2017) - Widbiller, M.; Eidt, A.; Lindner, S. R.; Hiller, K.‐A.; Schweikl, H.; Buchalla, W.; Galler, K. M.
Abstract: Aim: To establish a simplified and efficient protocol for the isolation and concentration of matrix proteins from human dentine, and to assess the effects of extracted dentine matrix proteins (eDMP) on the behaviour of human pulp cells. Methodology: Matrix proteins were isolated from human dentine, purified, concentrated and characterized with protein and enzyme‐linked immunosorbent assays (ELISA). Culture media were supplemented with eDMP in different concentrations, referred to as eDMP 1–10 000, to assess viability and proliferation of human pulp cells by DNA and MTT assays; apoptotic events were quantified by flow cytometry. Chemotactic effects of eDMP were assessed in a modified Boyden chamber assay. Expression levels of odontoblastic marker genes in pulp cells cultured with eDMPs were determined by real‐time quantitative PCR, and the ability to induce mineralization was demonstrated by alizarin red staining. Nonparametric statistical analysis was performed to pairwise compare different groups at all time‐points (Mann–Whitney U ‐test, α = 0.05). Results: High concentrations of eDMP exhibited significant antiproliferative effects ( P  ≤ 0.023) after 5 (eDMP 1000) and 7 days (eDMP 500) without affecting cell viability. Apoptosis was barely influenced ( P  ≥ 0.089). eDMP exerted a concentration‐dependent chemotactic stimulus on dental pulp cells with statistical significance already at low dosage ( P  = 0.006 at eDMP 10). Changes in gene expression indicated a differentiation into odontoblast‐like cells, which was corroborated by findings of mineral nodule formation. Conclusions: A novel, effective and time‐saving protocol for isolation and concentration of dentine matrix proteins is presented. As eDMP stimulates chemotaxis, differentiation and mineralization without affecting viability, endogenous dentine matrix proteins might be valuable for approaches to regenerate or engineer dental pulp.